Pengaruh Modifikasi Alat Latihan Dan Resistance Band Terhadap Akurasi Shooting Club SSB MIJ - Muhammad Damar Udin; Riswanto, A Heri; Kahar, Irsan; Hidayat, Rachmat (Universitas Hamzanwadi, 2025)
Low shooting accuracy is a problem faced by SSB MIJ players. This study aims to analyze the effect of modified training equipment (target net) and resistance bands on improving shooting accuracy. The method used is quantitative with a two-group pretest-posttest design. The sample consisted of 20 players divided into two groups. The measurement instrument used was the Bobby Charlton shooting test. The data were analyzed using a t-test with SPSS. The results showed that both training methods were significant in improving shooting accuracy. The t-value (8.260) was greater than the t-table (2.093) with a significance of 0.000 < 0.05. Only one player did not experience an improvement. The results of the independent sample t-test also showed a significant difference between the two groups. More specifically, the group that used the modified target net showed a more effective improvement than the group that used resistance bands. The conclusion of this study is that both the modified target net and resistance bands have a positive effect on shooting accuracy, but training with the target net proved to be more effective. Therefore, this modification of training equipment can be recommended to coaches as an applicable training method to improve the shooting accuracy of young soccer players.